Discussion of an integrated framework for multiple financial regulations - Tobias Adrian (Federal Reserve Bank of New York, 2012)
A 2012 paper by Goodhart, Kashyap, Tsomocos, and Vardoulakis (GKTV) proposes a dynamic general equilibrium framework that provides a conceptual - and to some extent quantitative - framework for the analysis of macroprudential policies. The distinguishing feature of GKTV's paper relative to any other on macroprudential policy is its study of a setting with multiple financial frictions that permits the analysis of multiple macroprudential policy tools at the same time. The modeling approach includes various market failures such as incomplete markets with heterogeneous agents, fire-sale externalities, and margin spirals, all of which provide rationales for policies designed to improve welfare. In GKTV's model, liquidity ratios are found to be more efficient preemptive tools than capital ratios or loan-to-value ratios. However, these liquidity ratios need to be relaxed in times of crises in order to reduce adverse effects from fire-sale externalities. It remains to be seen how robust these findings are in alternative, fully dynamic settings. Furthermore, GKTV's approach does not address the tension between micro- and macroprudential objectives, and the timing of the buildup and release of policies is not specified precisely.
Keywords: G18; G21; G28; 330; macroprudential policy; microprudential policy; procyclicality